Application of Evaluation and Feedback Methods to the Achievement of Lactation Massage Skills of Midwifery DIII Students - Desi Heriyana; Budu Budu; Werna Nontji; Sutrisno Sutrisno; Mardiana Ahmad; Andi Nilawati Usman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study aims to analyze the effect of the application of evaluation and feedback methods on the achievement of knowledge and skills of lactation massage in the intervention group and control group. This study used Quasi experimental design with pretest-posttest control group design. The sampling technique was quota sampling with a total of 44 second semester DIII midwifery students divided into two institutions, namely 22 students from Batari Toja Watampone Midwifery Academy as the intervention group and 22 students from Lapatau Midwifery Academy as the control group. The study was conducted during February-April 2023. Data were analyzed using Wilcoxon, Mann-witney, Chi-Squard and Kruskal wallis tests. The results of the study in the intervention group on knowledge achievement showed that 81.8% were lacking, 18.2% were sufficient and after the posttest assessment as many as 36.4% were sufficient and 63.3% were good with a value of P = 0.000, while for skill achievement in the pretest assessment 90.9% were sufficient, 9.1% were good then there was a change in the posttest assessment to 13.6% good and 86.4% very good with a value of p = 0.000. While the control group for knowledge achievement was 95.5% insufficient and 4.5% sufficient in the pretest and posttest assessments showing 54.5% insufficient, 27.3% sufficient and 18.2% good with a value of P = 0.008. Then for skill achievement as much as 100% was sufficient in the pretest assessment and increased to 40.9% good, 59.1% very good after the posttest with a value of P = 0.000. Based on the results obtained, it can be stated that the application of the evaluation and feedback method has a better effect on the learning outcomes of lactation massage.Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh penerapan metode evaluasi dan feedback terhadap capaian pengetahuan dan keterampilan pijat laktasi pada kelompok intervensi dan kelompok kontrol. Penelitian ini menggunakan desain Quasi eksperimen dengan rancangan pretest-posttest control group design. Teknik pengambilan sampel adalah quota sampling dengan jumlah 44 mahasiswa DIII kebidanan semester II yang terbagi atas dua institusi yaitu 22 mahasiswa dari Akademi kebidanan Batari Toja Watampone sebagai kelompok intervensi dan 22 mahasiswa Akademi Kebidanan Lapatau sebagai kelompok kontrol. Penelitian dilaksanakan selama bulan februari- April 2023. Data dianalisis menggunakan uji Wilcoxon, Mann-witney, Chi-Squard dan kruskal wallis. Hasil penelitian pada kelompok intervensi terhadap capaian pengetahuan menunjukkan sebanyak 81,8% kurang, 18,2% cukup dan setelah penilaian posttest sebanyak 36,4% cukup dan 63,3% baik dengan nilai P=0,000, sedangkan untuk capaian keterampilan pada penialian pretest 90,9% cukup, 9,1% baik kemudian terjadi perubahan pada penilaian posttest menjadi 13,6% baik dan 86,4% sangat baik dengan nilai p=0,000. Sementara kelompok kontrol untuk capaian pengetahuan sebanyak 95,5% kurang dan 4,5% cukup pada penilaian pretest dan posttest menunjukkan 54,5% kurang, 27,3% cukup dan 18,2% baik dengan nilai P=0,008. Kemudian untuk capaian keterampilan sebanyak 100% cukup pada penilaian pretest dan meningkat menjadi 40,9% baik, 59,1% sangat baik setelah posttest dengan nilai P=0,000. Berdasarkan hasil yang diperoleh dapat dinyatakan bahwa penerapan metode evaluasi dan feedback memiliki pengaruh yang lebih baik dalam capaian pembelajaran pijat laktasi.